2022
DOI: 10.1007/s12975-021-00977-3
|View full text |Cite|
|
Sign up to set email alerts
|

Comparative Studies of Cerebral Reperfusion Injury in the Posterior and Anterior Circulations After Mechanical Thrombectomy

Abstract: Cerebral reperfusion injury is the major complication of mechanical thrombectomy (MT) for acute ischemic stroke (AIS). Contrast extravasation (CE) and intracranial hemorrhage (ICH) are the key radiographical features of cerebral reperfusion injury. The aim of this study was to investigate CE and ICH after MT in the anterior and posterior circulation, and their effect on functional outcome. This is a retrospective study of all consecutive patients who were treated with MT for AIS at University of California Irv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 45 publications
4
7
0
Order By: Relevance
“…al 8 . Nevertheless, increased mortality was observed in PMT in both: individual studies 5,6,13 and meta-analyzes 7,14 .…”
Section: Resultsmentioning
confidence: 98%
“…al 8 . Nevertheless, increased mortality was observed in PMT in both: individual studies 5,6,13 and meta-analyzes 7,14 .…”
Section: Resultsmentioning
confidence: 98%
“…The existence of an ischemic penumbra (metabolically viable brain tissue that may be salvageable with cerebral blood flow restoration) is the fundamental rationale for reperfusion therapy and hence, measurement of the volume of penumbra salvage may offer a further opportunity to directly compare treatment effects. The effect of EVT on functional outcome is still not entirely understood, also considering factors beyond vessel recanalization such as the degree of tissue injury including the phenomenon of reperfusion injury 20. The most widely used imaging biomarker to describe and compare treatment effects is currently total infarct volume.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 However, reperfusion injury is the main complication of concern after the procedure, which may cause intracranial hemorrhage (ICH) and is associated with severe neurological deterioration. 3 Either hemorrhagic or transient contrast extravasation is frequently observed on noncontrast brain computer tomography (CT) after intra-arterial intervention. It is critical to distinguish these two imaging phenomenons.…”
Section: Introductionmentioning
confidence: 99%
“…It is critical to distinguish these two imaging phenomenons. 3 A few studies have indicated that contrast extravasation with a hyperdense lesion with a maximum Hounsfield unit (HU) measurement >90 on the immediate brain CT after an intra-arterial intervention is highly associated with the occurrence of parenchymal hematoma. [4][5][6] Yoon et al 6 assumed that contrast accumulation is associated with disruption of the blood-brain barrier, 5 and the patterns of contrast accumulation may differ between patients with and without further symptomatic ICH.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation